THE NEXUS BETWEEN SUSTAINABLE VALUE CHAIN ACTIVITIES AND FINANCIAL BENEFITS OF THE SOYBEAN VALUE CHAIN SYSTEM IN THE NORTHERN REGIONS OF GHANA - Ghartey, William; Owusu, Rebecca; Ahmed, Ben; Atala, TK (Applied Studies in Agribusiness and Commerce, 2023)
Soybean is an important crop that contributes to economic freedom and food security. The study of soybean value chain is therefore important to improve on the activities of the chain actors for an overall economic gains. This paper aims to examine the nexus between sustainable value chain and financial benefits of the soybean value chain system in Ghana. Specifically, we employ the triple bottom line model to examine the soybean value chain from economic, social and environmental perspectives using sample data from Ghana. With a sample size of 300 including all actors of the value chain, our findings reveal that chain actors do not differ in their perceptions of overall financial gains that accrued to them with their involvement in chain economic activities. The findings further revealed that perceived financial sustainability of chain activities was affected by tangible financial benefits. Moreover, the results further show that chain actors’ perception of social sustainability performance was significantly affected by expected overall financial gains that accrue to them as a result of their participation in chain economic activities.